INNV-32. ACCESS TO SPECIALTY RADIATION CARE FOR PATIENTS WITH RESECTABLE BRAIN TUMORS. (12th November 2021) - Choi, Mehee; Martin, Brian; Zabramski, Joseph; Misell, Lisa; Brachman, David
Abstract: INTRODUCTION: Many patients with brain tumors face challenges with access to care. For rural patients, prolonged travel times may limit access to appropriate radiotherapy. Radiation centers (RCs) offering specialized brain radiotherapy, e.g., stereotactic radiosurgery (SRS), are geographically limited. Brain brachytherapy at the time of resection offers an option for such patients, but technical challenges have limited the adoption. To address the limitations of traditional brachytherapy, a device with Cs-131 seeds embedded in a bioresorbable collagen tile (GammaTile (GT), GT Medical Technologies, Tempe, AZ) was developed. The device is FDA-cleared for permanent implantation at the time of resection for all recurrent intracranial tumors and newly diagnosed malignant intracranial neoplasms. To investigate if wider availability of this treatment could possibly lower the geographic barrier to access to care, we mapped the US population against existing RCs with brain tumor expertise and neurosurgery centers (NSCs) performing craniotomies. METHODS: We analyzed 2018 CMS claims data using CPT codes for single- and multi-fraction SRS to identify RCs with brain tumor treatment expertise and mapped these against the population. Using similar methodology, using CPT codes for craniotomies, we identified NSCs, as any facility performing craniotomies is potentially eligible to implant the device. RESULTS: 135 RCs used CPT codes for SRS. 193-, 119-, 82-, and 52-million Americans lived >30-, >60-, >90-, and >120-minutes from one of these centers, respectively. 530 NSCs preform craniotomies, including ≥ 1 in every state, a 4-fold increase over the number of RCs offering SRS. CONCLUSIONS: For many patients, substantial travel distances limit access to RCs with brain tumor treatment expertise. In contrast, the 530 craniotomy-performing NSCs have far greater geographic dispersion. The option of undergoing brain radiation with GT implantation at the time of brain tumor craniotomy brings treatment closer to millions, ensures compliance, and reduces additional travel for follow-up radiation treatment.